Iconomy : towards a political economy of images - Smith, Terry (Terry E.) (Anthem symploke studies in theory, 2022)
Iconomy: Towards a Political Economy of Images argues that imagery of all kinds has become a definitive force in the shaping of contemporary life. While immersed in public politics and private imaginaries, such imagery also operates according to its own logic, potentialities, and limitations. This book explores viral imagery-the iconopolitics-of the pandemic, US Presidents Trump and Biden, Black Lives Matter, as well as the rise of a 'black aesthetic' in white artworlds. Having arrived at the term 'iconomy' in the years just prior to 9/11, and tracking its growing relevance since then, Smith argues that its study does not require a discipline serving nation states and globalizing capitalism but, instead, a deconstructive interdiscipline that contributes to the politics of planetary world-making.